Ó pátria amada, idolatrada, salve! Salve! : festas escolares e comemorações cívicas na Paraíba (1937-1945) - Silva, Vânia Cristina da (2011)
This work is linked to the research of Teaching History and Historical understanding of the Graduate Program in History from the Federal University of Paraíba - UFPB, with a major in History and Historical Culture, it aims is to analyze the school parties and civic celebrations in Paraíba during the New State (1937-1945).We seek to emphasize the importance given to the parties that functioned as essential tools in training and dissemination of a national education, patriotic, civic and service of a moralizing estanovismo . From the articles published in the pages of A União newspaper, A Imprensa, Revista do Ensino, as well as in our references, we discuss the social, cultural and civic celebrations that the policies have had on society in Paraiba, because this type of celebration went beyond the school s walls involving also the local community. While in effect, the dictatorial government of Getúlio Vargas and his staff and stakeholders were responsible for some changes in the festival calendar of the schools, this means that besides the existing dates that we selected to work here, as the Day of Fatherland, Day Work, Flag Day and Arbor Day, new holidays have been added, there was then we prefer to call the invention of new traditions, a concept used by Hobsbawm (1997) and adopted by us as a way to better understand how these changes occurred in the civic calendar and festive and cultural life in school. Among these new holidays invented give prominence to the anniversary of Getúlio Vargas (April 19), anniversary of establishment of the New State (Nov. 10), Youth Day (April 19) and Race Day (celebrated in the homeland of the Week). In this scenario of changes and amendments, the big parades have become a constant in Paraíba streets, these streets that at times of celebration, had a euphoric movement of people who thronged the quest to see the students marching in salute of the ideals New State Policy.